Allylic alcohol synthesis by gas-phase hydrogen transfer reduction of unsaturated ketones - Di Cosimo, Juana Isabel (2005)
The gas-phase hydrogen transfer reduction (HTR) of mesityl oxide (MO) with 2-propanol to selectively obtain allylic alcohols was studied on MgO. MO was converted directly to 4-methyl-3-penten-2ol (UOL1) or isomerised to iso-mesityl oxide (i-MO), which consecutively formed 4-methyl-4-penten-2ol (UOL2). Significant amounts of methyl isobutyl carbinol (MIBC) were also formed by the simultaneous reduction of CC and CO groups of MO. The effect of reaction conditions on catalyst activity and selectivity was determined in order to improve total UOL yield that was about 28% under standard reaction conditions (T = 523 K, 2-propanol/MO = 5, W/FMO0 = 15 g h/mol). Total UOL yield increased continuously with contact time up to 42% but when the 2-propanol/MO ratio was varied, UOL yield reached a maximum at a reactant ratio of about 4. UOL2 yield markedly increased with temperature at expenses of MIBC. The increase of temperature also improved the catalyst stability because suppressed formation of coke intermediates. Regarding the effect of the hydrogen donor, higher total UOL yields were obtained by using secondary alcohols, such as 2-propanol and 2-butanol, than primary (1-propanol) or secondary aryl (1-penylethanol) alcohols.